A combined FSTRA-shotgun proteomics approach to identify molecular changes in zebrafish upon chemical exposure - Ayobahan, Steve U.; Eilebrecht, Elke; Kotthoff, Matthias; Baumann, Lisa; Eilebrecht, Sebastian; Teigeler, Matthias; Hollert, Henner; Kalkhof, Stefan; Schäfers, Christoph (Scientific reports, 2019)
The fish short-term reproduction assay (FSTRA) is a common in vivo screening assay for assessing endocrine effects of chemicals on reproduction in fish. However, the current reliance on measures such as egg number, plasma vitellogenin concentration and morphological changes to determine endocrine effects can lead to false labelling of chemicals with non-endocrine modes- of-action. Here, we integrated quantitative liver and gonad shotgun proteomics into the FSTRA in order to investigate the causal link between an endocrine mode-of-action and adverse effects assigned to the endocrine axis. Therefore, we analyzed the molecular effects of fadrozole-induced aromatase inhibition in zebrafish (Danio rerio). We observed a concentration-dependent decrease in fecundity, a reduction in plasma vitellogenin concentrations and a mild oocyte atresia with oocyte membrane folding in females. Consistent with these apical measures, proteomics revealed a significant dysregulation of proteins involved in steroid hormone secretion and estrogen stimulus in the female liver. In the ovary, the deregulation of estrogen synthesis and binding of sperm to zona pellucida were among the most significantly perturbed pathways. A significant deregulation of proteins targeting the transcriptional activity of estrogen receptor (esr1) was observed in male liver and testis. Our results support that organ- and sex-specific quantitative proteomics represent a promising tool for identifying early gene expression changes preceding chemical-induced adverse outcomes. These data can help to establish consistency in chemical classification and labelling.
Gesehen am 24.03.2020